A Meta-Analysis of Folic Acid in Combination with Anti-Hypertension Drugs in Patients with Hypertension and Hyperhomocysteinemia - Wang, Wen-Wen; Wang, Xin-Shi; Zhang, Zeng-Rui; He, Jin-Cai; Xie, Cheng-Long (Frontiers in Pharmacology, 2017)
Folic acid is generally used to lower homocysteine concentrations and prevent stroke and cardiovascular disease (CVD) at present. However, the eﬃcacy of therapies that lower homocysteine concentrations in reducing the risk of CVD and stroke remains controversial. Our objective was to do a meta-analysis of relevant randomized controlled trials (RCTs) to evaluate the efficacy of folic acid supplementation among patients with hypertension and Hyperhomocysteinemia (HT/HHcy). We included RCTs examining the effects of folic acid plus antihypertensive therapy compared to antihypertensive alone. Weighted Mean Difference (WMD) and Relative risk (RR) were used as a measure of the effect of folic acid on the outcome measures with a random effect model. Sixty-five studies including 7887 patients met all inclusion criteria. Among them, 49 trials reported signiﬁcant effect of combination therapy for reducing SBP (systolic Blood Pressure) and DBP (Diastolic Blood Pressure) levels compared with antihypertensive alone (WMD =-7.85, WMD =-6.77, respectively). Meanwhile, folic acid supplementation apparently reduced the level of total homocysteine (WMD =5.5). In addition, folic acid supplementation obviously reduced the risk of cardiovascular and cerebrovascular events (CVCE) by 12.9% compared with control groups. In terms of the stratiﬁed analyses, a bigger beneﬁcial eﬀect was seen in those RCTs with treatment duration of more than 12 weeks, a decrease in the concentration of total homocysteine of more than 25%, with folic acid fortiﬁcation. Our findings indicated that folic acid supplementation was effective in the primary prevention of CVCE among HT/HHcy patients, as well as reducing the blood pressure and total homocysteine levels.